PENGARUH LINGKUNGAN BELAJAR SEKOLAH DAN MOTIVASI BELAJAR TERHADAP KEMANDIRIAN BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SD NEGERI 14 BENGKULU SELATAN - Erlina Zanita (IAIN Bengkulu, 2018)
This research is motivated by the independence of learning that is realized by every student, but this is not optimal, especially in learning Islamic Religious Education. The role of school learning environment is very influential on the success of the learning process, in addition to the low learning motivation to be one of the factors that make students have not achieved the independence of learning Islamic Education maximum. The purpose of this research is first to know the influence of school learning environment to the independence of learning Islamic Religious Education to students in SD Negeri 14 Bengkulu Se- latan, secondly to know the influence of learning motivation to self-reliance learning Islamic Religion on students at SD Negeri14 Bengkulu Selatan, third to know A simultaneous positive influence between school learning environments and learning motivation on the independence of learning Islamic Religious Education on students at SD Negeri 14 Bengkulu Selatan. With correlation coefficient between X2 and Y equal to 0,787 which show strong correlation and correlation equal to 62,0%. Thirdly, there is simultaneously an influence between school learning environment and learning motivation toward self-reliance learning of Islamic Religious Education in SD Negeri 14 Bengkulu Selatan with correlation coefficient between X1 and X2 together to Y equal to 0,808 which shows at very strong relation level with correlation equal to 65 , 4% and Y regression result of X1 and X2, regression equation obtained Y = 5,498 + 0,229 + 0,627